From Self to Social Sphere: Inner Peace and the Dynamics of Conflict - Andar Ifazatul Nurlatifah; Ahman Ahman; Syamsu Yusuf; Ilfiandra Ilfiandra (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
This study aims to examine the influence of inner peace on the dynamics of conflict experienced by university students, including both intrapersonal and interpersonal conflicts. The research employed a quantitative approach with a non-experimental correlational design. A total of 82 students participated, selected through purposive sampling, consisting of 35 students residing in Islamic boarding schools and 47 non-resident students. The Inner Peace Scale, covering the aspects of acceptance of loss, inner balance and calmness, and transcending hedonism and materialism, was tested on 438 students and produced 19 valid items based on Pearson correlation validity and a Cronbach’s Alpha reliability score of 0.764. The Decisional Conflict Scale (DCS), tested on 35 students, resulted in 15 valid items with a reliability of 0.914. The Interpersonal Conflict Scale, adapted from the Thomas-Kilmann Conflict Mode, yielded 29 valid items with a reliability of 0.932. Normality testing using the Shapiro-Wilk test confirmed normal data distribution. Pearson correlation analysis revealed that inner balance and calmness had a significant positive correlation with intrapersonal conflict (r = 0.437; p = 0.009), while acceptance of loss had a significant negative correlation with interpersonal conflict (r = -0.433; p = 0.009). The regression analysis showed that the model significantly explained intrapersonal conflict (RÂ² = 0.361, p < 0.001), with two dimensions of inner peace having significant effects: inner balance and calmness (Î² = 0.665, p < 0.001) and transcending hedonism and materialism (Î² = -0.489, p = 0.002). For interpersonal conflict, only the acceptance of loss dimension showed a significant negative effect (Î² = -0.364, p = 0.033). These findings suggest an opportunity to reinforce empathic and transformative communication approaches, emphasizing both conflict resolution and the personal transformation of those involved in the conflict.